Enhancing Employee Performance through Competence and Work Climate: Implications for Human Resource Management - Suci Ramadhan; Lindanur Sipatu; Rosida Adam; Arie Kurniawan (Journal of Educational Management Research, 2025)
This study aims to analyze the influence of competence and work climate on employee performance at the Community Health Center. The research background highlights the importance of employee competence and a supportive work climate in achieving optimal performance, considering the existing issues such as inconsistent adherence to operational procedures. Data were collected using a questionnaire that had been tested for validity and reliability. The variables examined include competence (knowledge, skills, attitude, and values), work climate (reward, support, commitment), and employee performance (quality, quantity, task implementation). The data were analyzed using multiple linear regression in SPSS version 27. The results of the study are expected to show that competence and work climate have a significant partial and simultaneous influence on employee performance. The findings are expected to contribute to improving human resource quality, strengthening the work environment, and optimizing public service delivery at the Community Health Center. The implications of this research for educational management highlight the importance of integrating competence development and fostering a favorable work climate in academic institutions. By prioritizing these factors, educational managers can enhance teacher performance, improve service quality, and create a conducive environment for optimal learning outcomes.